Pemanfaatan Siaran Langsung Instagram sebagai Media Edukasi Kesehatan Ibu Hamil melalui Akun @bumil_pintar - Ihsan, Satria Noor; Aminah, Siti (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Access to trustworthy health information remains a persistent concern for expectant mothers in Indonesia. In response, an interactive educational initiative was implemented via Instagram Live on the @bumil_pintar account, airing twice weekly from February 3 to May 31, 2025. Across 32 sessions, viewership grew from 64 to 301 per session, with comments rising from 5 to 20. In total, the broadcasts engaged 5,475 viewers and generated 417 comments. While no formal statistical tests were applied, the upward trend in participation is evident. Real-time interaction and steady scheduling set this approach apart from conventional one-way digital education. These findings offer a foundation for strengthening maternal health literacy in digital community settings. Ongoing assessment will be necessary to evaluate its quantitative impact.